Teaching and learning with AI: a qualitative study on K-12 teachers' use and engagement with artificial intelligence - Tripathi, Tarang; Sharma, Smriti R.; Singh, Vatsala; Bhargava, Palaash; Raj, Chandraditya (Frontiers in Education, 2025)
IntroductionAs artificial intelligence technologies rapidly enter educational settings, teachers find themselves navigating fundamental pedagogical shifts while maintaining professional agency. Despite growing AI adoption in schools, limited research examines how teachers actually experience and shape AI integration within their classroom contexts, especially in the contexts of developing countries. This study investigates teachers' beliefs about AI's educational role, their incorporation patterns, and associated challenges and opportunities.MethodsUsing semi-structured interviews with 20 teachers from two private schools in Delhi, India, the paper employed thematic analysis grounded in an AI Literacy and Ecological Teacher Agency Framework.Findings/ResultsThree key findings emerged: Teachers simultaneously embrace AI's potential to enhance learning and administrative efficiency while expressing deep concerns about student over-dependence and erosion of critical thinking skills. Both teachers and students demonstrate emerging technical AI competencies, but significant gaps in critical evaluation and ethical application remain, revealing a concerning literacy imbalance. Beyond surface-level tool adoption, AI integration fundamentally reshapes teachers' professional beliefs and sense of agency, prompting ongoing renegotiation of their pedagogical identities and classroom authority.DiscussionThe findings demonstrate an urgent need for teacher education that centers the teacher rather than the technology and moves beyond basic technical training to embed critical thinking and ethical reasoning into AI engagement. Parallel to this, policymakers must prioritize collaborative frameworks that position teachers as partners in AI integration design rather than passive recipients of top-down mandates. The paper concludes with a call for future research to examine AI integration across diverse educational contexts to understand how institutional and socioeconomic factors shape teachers' engagement with AI technologies.